2023
DOI: 10.1039/d2bm01625g
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional black phosphorus-based adhesive patch intrinsically induces partial EMT for effective burn wound healing

Abstract: The ultimate goal of cutaneous wound healing is to reform a stratified epithelium to restore the normal epidermal barrier, which involves the epithelial-to-mesenchymal transition (EMT) process. However, the healing strategies...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Neovascularisation plays an essential role in the later stage of wound healing. 55,56 Immunohistochemical staining for CD31, a vascular endothelial cell differentiation and maturation marker, was used to evaluate neovascularization formation at the wound site. As shown in Fig.…”
Section: Wound Healing In Vivo Of Ag/zn@plamentioning
confidence: 99%
“…Neovascularisation plays an essential role in the later stage of wound healing. 55,56 Immunohistochemical staining for CD31, a vascular endothelial cell differentiation and maturation marker, was used to evaluate neovascularization formation at the wound site. As shown in Fig.…”
Section: Wound Healing In Vivo Of Ag/zn@plamentioning
confidence: 99%
“…For instance, Wang et al have analyzed the efficacy of photothermal burn wound treatment using a catechol-conjugated chitosan and dextran-based hydrogel containing black phosphorus nanosheets. [135] Besides its robust tissue adhesiveness due to catechol functionalization, the encapsulated black phosphorus radiated heat upon NIR laser irradiation, which promoted a photothermal antibacterial effect against four main bacteria that often cause wound infection, Staphylococcus aureus, Escherichia coli, methicillin-resistant S. aureus, and Pseudomonas aeruginosa, without damaging the surrounding tissues. Accordingly, applying hydrogel to a cutaneous infectious burn wound model followed by NIR irradiation induced antiinflammation and rapid re-epithelialization, contributing to a remarkable wound closure rate and accelerated restoration of skin morphology and demonstrating the therapeutic significance in bioadhesive hydrogel-based PTT.…”
Section: Hydrogels For Nir-induced Therapymentioning
confidence: 99%
“…The EMT has been reported to be ubiquitous in organ fibrosis and wound healing [ 117 , 118 ]. Wang et al [ 119 ] found that black phosphorus nanosheets (BPNSs), a new EMT-inducing system integrates, promoted burn wound healing by inducing EMT of epithelial cells through the Snail1-mediated signaling pathway. Recently, the change in the EMT was observed in the keloid tissues [ 120 ].…”
Section: The Roles Of Hif-1α In Keloids Formationmentioning
confidence: 99%